The Evolution of Nature in High Medieval Art and Christian Eschatological Theories (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
This paper first presents an overview about the evolution of the representation of nature in European artistic culture of the High Middle Ages. A result of this is the detection of a paralysis in the aesthetic evolution of nature in visual arts after previous phases of decorative and symbolic richness. Different historiographic proposals on the evolution of the relationship between man and nature in the Middle Ages show a possible contextualization with the artistic paralysis we have stated. That path leads to the search for a relation of the phenomenon detected with the theological foundations of the monastic culture and its eschatological discourses.
Keywords: Nature in Visual Arts; High Middle Ages; Eschatology